Multilocus Sequence Typing of Enterocytozoon bieneusi Isolates From Various Mammal and Bird Species and Assessment of Population Structure and Substructure - Liu, Xiaohua; Wu, Yanchen; Yang, Fengkun; Gong, Baiyan; Jiang, Yanyan; Zhou, Kexin; Cao, Jianping; Zhang, Weizhe; Liu, Aiqin; Shen, Yujuan (Frontiers in Microbiology, 2020)
Enterocytozoon bieneusi is one of the most common intestinal pathogens in humans and animals. E. bieneusi has been confirmed to be complex microsporidian species. Approximately 500 ITS genotypes of E. bieneusi have been defined. With the establishment and application of multilocus sequencing typing and population genetic tools in E. bieneusi, the studies on these aspects have been carried out worldwide, but little information is available. To understand genetic variation of mini-/micro-satellites and the population structure and substructure of E. bieneusi in northeastern China, 305 E. bieneusi DNA specimens composed of 28 ITS genotypes were from 13 mammal species and five bird species in the investigated areas. They were characterized by nested-PCR amplification and sequencing at four mini-/micro-satellite loci (MS1, MS3, MS4 and MS7). At the MS1, MS3, MS4 and MS7 loci, 153 (50.16%), 131 (42.95%), 133 (43.61%) and 128 (41.97%) DNA specimens were amplified and sequenced successfully with 44, 17, 26 and 24 genotypes being identified, respectively. Multilocus genotypes (MLGs) showed a higher genetic diversity than ITS genotypes. 48 MLGs were produced out of 90 ITS-positive DNA specimens based on concatenated sequences of all the five genetic loci including ITS. Linkage disequilibrium (LD) and limited genetic recombination were observed by measuring LD using both multilocus sequences and allelic profile data, indicating an overall clonal population structure of E. bieneusi in the investigated areas. These data will aid in the longitudinal tracking of the attribution of source of infection/contamination and in elucidating transmission dynamics, and will provide valuable information for making efficient control strategies to intervene with and prevent occurrence of microsporidiosis caused by E. bieneusi among animals and transmission of E. bieneusi from animals to humans in the investigated areas. Phylogenetic and network analyses identified three different subgroups, revealing the presence of host-shaped segregation and the absence of geographical segregation in E. bieneusi population. Meanwhile, the MLGs from zoonotic ITS genotypes were observed to be basically separated from the MLGs from host-adapted ones. Assessment of substructure will have a reference effect on understanding of zoonotic or interspecies transmission of E. bieneusi and evolution direction from zoonotic genotypes to host-adapted genotypes.